UPAYA INDONESIA MENINGKATKAN EKSPOR KAYU MANIS KE SINGAPURA TAHUN 2018-2020 - Putri Yuliana; M. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research describes Indonesia's efforts to increase cinnamon exports to Singapore. There was a decline in Indonesian cinnamon exports to Singapore in 2018-2020, which was 1,034,806 USD in 2018 decreasing to 799, 412 USD in 2019 and in 2020 to 788, 829 USD. The decline was influenced because there are still obstacles related to the quality standards of cinnamon produced by Indonesia. Indonesian cinnamon in meeting export demand has not been of high quality due to the fact that cinnamon still contains remnants of insects/dirt, fungi or herbicide residues. Cinnamon plantation area in Indonesia also tends to decrease. The decrease in land area is influenced by people who harvest cinnamon by harvesting tilled or clear cutting and the transfer of land functions which can result in the number of cinnamon trees decreasing. The author collects data from books, academic journals, theses, and sources from the internet related to research issues regarding Indonesia's efforts to increase cinnamon exports to Singapore. The author uses the perspective of pluralism and the level of analysis of the nation state, while the theory used in this study is the theory of comparative advantage.This research shows that Indonesia's efforts to increase cinnamon exports are carried out through improving the quality of Indonesian cinnamon by establishing quality standards and releasing superior varieties, increasing the quantity and quality of Indonesian spices, utilizing Indonesian trade representatives in Singapore and promoting Indonesian spices such as the use of digital platforms and the Trade Expo Indonesia trade show. Keywords: Indonesian Cinnamon Export, Indonesia Export to Singapore, Indonesian Spice Trade, Cinnamon Spice, Cinnamon Industry.